How Does Cognitive Behavior Therapy view an Academic Anxiety of The Undergraduate Thesis? - Situmorang, Dominikus David Biondi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2018)
The undergraduate thesis is still a terrifying final project for most millennials college students. Many of them are procrastinating, avoiding their supervisors, doing non-productive things as a form of anxiety diversion, and the most extreme is to committing suicide as a result of excessive academic anxiety. The educational counselors as one of the college internal agents is expected to solve the problems that often occured. Based on Cognitive Behavior Therapy (CBT) approach, the academic anxiety of the undergraduate thesis experienced by millennials college students is a cognitive distortion caused by maladaptive core beliefs. Therefore, what we need to know more about how CBT view an academic anxiety of the undergraduate thesis as a problem, so that counselors in Indonesia will be able to understand conceptually before do practice of healing counseling to help the millennials college students to be free from this problem in the future. This research uses descriptive analysis and Focus Group Discussion (FGD) approach. The result of this research is CBT-Based Music can help millennials college students to restore cognitive, affective, and behavioral functions to be adaptive again, so millennials college students are expected to independently optimize their potential, in order to reduce academic anxiety and solve the undergraduate thesis well.